Análisis de la calidad de los servicios de la empresa de telecomunicaciones transtelco por medio de la construcción de un Software basado en el modelo de medición servqual - Ureta Santillán, Carlos (2014)
This research 's main objective was to develop a tool to measure the perception of service Transtelco customers to continuously improve the care provided by the company. The telecommunications sector has grown considerably in recent years in the country , for which the Government has created various agencies that monitor this activity. The National Telecommunications Council is the highest body governing telecommunications in the country. This organism requires quality parameters at supplier companies must meet to their clients . This definitely makes these companies currently established quality standards that allow continuous improvement of the same . Transtelco is a company that provides internet services in several provinces , but the population that I use is the one corresponding to the city of Quevedo where 20 surveys method SERVQUAL was applied to define the gaps between the service expected and received. Based on the results it can be concluded that the system facilitates the development of SERVQUAL instrument and also displays a report that presents visually 5 gaps easier to read them